Penerapan Program Accurate Accounting Pada CV Digital Dimensi Bogor : DALAM KONTEKS LAPORAN PEMBELIAN BARANG DAGANG - Apriyanti, Riska Dwi; Pramiudi, Udi (Jurnal Aplikasi Bisnis Kesatuan, 2025)
Accurate Accounting is an accounting program designed to facilitate accountants in completing corporate financial statements. By applying the Accurate Accounting program, companies can easily ensure financial control, improve data accuracy, facilitate decision-making, and improve data reliability. The purpose of this final task is to explain the sales accounting system applied by the CV Digital Dimensi Bogor and to apply the Accurate Accounting program in the recording of the merchandise purchase report on the CV Digital Dimensi Bogor. These observations show that by applying the Accurate Accounting program to the CV Digital Dimensi Bogor it facilitates the recording and reporting of goods purchase transactions that were previously still using manual recording methods. With these complete modules, Accurate Accounting can make company performance more effective and efficient in merchandise purchasing activities. It can make it easier for the company to make the next decision quickly and accurately.   Keywords: merchandise purchases, accurate.